First and second doses of Covishield vaccine provided high level of protection against SARS-CoV-2 infection in highly transmissible settings: results from a prospective cohort of participants residing in congregate facilities in India. Issue 5 (24th May 2022) - Tsundue, Tenzin; Namdon, Tenzin; Tsewang, Tenzin; Topgyal, Sonam; Dolma, Tashi; Lhadon, Dekyi; Choetso, Tsering; Woesal, Tenzin; Yangkyi, Tenzin; Gupta, Amita; Peters, David; Paster, Zorba; et al.
Abstract : Objectives: This study aimed to determine the effectiveness of Covishield vaccine among residents of congregate residential facilities. Design: A prospective cohort study in congregate residential facilities. Setting: Dharamshala, Himachal Pradesh, India, from December 2020 to July 2021. Participants: Residents of all ages in seven facilities—three monasteries, two old age homes and two learning centres—were enrolled. Exposures: First and second doses of Covishield vaccine against SARS-CoV-2 infection. Main outcomes measures: Primary outcome was development of COVID-19. Secondary outcome was unfavourable outcomes, defined as a composite of shortness of breath, hospitalisation or death. Vaccine effectiveness (%) was calculated as (1−HR)×100. Results: There were 1114 residents (median age 31 years) participating in the study, 82% males. Twenty-eight per cent (n=308/1114) were unvaccinated, 50% (n=554/1114) had received one dose and 23% (n=252/1114) had received two doses of Covishield. The point prevalence of COVID-19 for the facilities ranged from 11% to 57%. Incidence rates (95% CI) of COVID-19 were 76 (63 to 90)/1000 person-months in the unvaccinated, 25 (18 to 35)/1000 person-months in recipients of one dose and 9 (4 to 19)/1000 person-months in recipients of two doses. The effectiveness of first and second doses of Covishield were 71% (adjusted HR (aHR) 0.29; 95% CI 0.18 to 0.46; p<0.001) and 80% (aHR 0.20; 95% CI 0.09 to 0.44; p<0.001), respectively, against SARS-CoV-2 infection and 86% (aHR 0.24; 95% CI 0.07 to 0.82; p=0.023) and 99% (aHR 0.01; 95% CI 0.002 to 0.10; p<0.001), respectively, against unfavourable outcome. The effectiveness was higher after 14 days of receiving the first and second doses, 93% and 98%, respectively. Risk of infection was higher in persons with chronic hepatitis B (aHR 1.78; p=0.034) and previous history of tuberculosis (aHR 1.62; p=0.047). Conclusion: Covishield was effective in preventing SARS-CoV-2 infection and reducing disease severity in highly transmissible settings during the second wave of the pandemic driven by the Delta variant.